Analysis of fertilizer application on soil heavy metal concentration in coffee plantation / Nur Hanini Hamzah - Hamzah, Nur Hanini (Faculty of Applied Sciences, 2017)
Agricultural activities use a large amount of chemicals such as fertilizer and pesticides. The application of fertilizer may result in the increase of Cd, Cr, Cu, Zn and Pb. The objective of this study was to investigate the variability concentration of these heavy metals pollution in soil increases due to application of fertilizer. Then, this study also was done to analyze the impact of heavy metal concentration from chemical fertilizer using geochemical approaches and contamination factor. Samples of soil were collected from coffee plantation located at Pusat Penyelidikan Pertanian Tun Abdul Razak, (PPPTR) Jengka. The result from analysis using ICP-OES indicated that Cd, Cr, Cu, Zn and Pb concentrations in soil were slightly differences and increased due to fertilizer application. The level determined by geo-accumulation index is uncontaminated. While contamination factor parameter indicate all classes of heavy metals involved.